Contribution of landfalling tropical system rainfall to the hydroclimate of the eastern U.S. Corn Belt 1981–2012 - Olivia Kellner; Dev Niyogi; Frank D. Marks (Weather and Climate Extremes, 2016)
This study provides a climatology (1981–2012) of landfalling tropical systems in the eastern U.S. Corn Belt and investigates the total contribution of these storms to the monthly climatological rainfall in the Midwestern United States. The primary focus is on rainfall impacts from landfalling tropical systems on historic corn yields at the climate division and crop reporting district level. Climatologically dry to drought conditions for historic monthly observed rainfall are identified using the Palmer Drought Severity Index (PDSI) and the Standardized Precipitation Index (SPI). It was found that without landfalling tropical system rainfall, the percentage increase in climatologically dry (or drier) conditions across the domain at state climate division resolution increased from 16% up to over 200%. The study also considers the effects of climatologically wet conditions on crop yields. Landfalling tropical system rainfall accounts for approximately 20% of the observed monthly rainfall during the tropical storm season (June–November) across the eastern U.S. Corn Belt (1981–2012). Correlation between the annual number of landfalling tropical systems and annual yield by state results in no relationship, but correlation of August monthly observed rainfall by climate division to crop reporting district annual yields has a weak to moderate, statistically significant correlation in Ohio districts 30–60 and Indiana CRD 90. ANOVA analysis suggests that landfalling tropical rainfall may actually reduce yields in some state's climate divisions/crop reporting districts while increasing yield in others. Results suggest that there is a balance between landfalling tropical storms providing sufficient rainfall or too much rainfall to be of benefit to crops. Findings aim to provide information to producers, crop advisers, risk managers and commodity groups so that seasonal hurricane forecasts can potentially be utilized in planning for above or below normal precipitation during phenologically important portions of the growing season.